Systems of variational inequalities and multiple-set split equality fixed-point problems for countable families of multivalued type-one mappings of the demicontractive type - Izuchukwu, C.; Mewomo, O. T.; Okeke, C. C. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.9 Our main aim is to introduce an iterative algorithm for the approximation of a common solution to a split-equality problem for finite families of variational inequalities and the split equality fixed-point problem. By using our iterative algorithm, we state and prove a strong convergence theorem for the approximation of an element in the intersection of the set of solutions of the split-equality problem for finite families of variational inequalities and the set of solutions of the split equality fixed-point problem for countable families of multivalued type-one mappings of the demicontractive type. Finally, we apply our result to study related problems. Our result supplements and extends some recent results in the literature.